Geometrical effect on the behavior of circular and elliptic tubes under dynamic axial loading. - Mat, Fauziah; Siregar, Rakhmad Arief; Ismail, K. A.; Yaacob, Sazali; Ahmad, M.; Othman, Inayatullah (2012)
A numerical investigation of circular and elliptic tubes is performed under dynamic axial loading using nonlinear finite element code LS DYNA. The material of the tubes is treated as piecewise linear elastic. The model developed is validated with earlier numerical results. The influence of geometrical parameters such as wall thickness, semi apical angle and cross section on the load carrying capacity of the structures is evaluated. The tubes are varying with thicknesses between 0.5 to 0.9 mm and semi apical angles between 0 to 10 degrees throughout their height. The results showed distinctive performance characteristics of straight and conical tubes of elliptic and circular shapes. The findings of this study would assist the future development of thin-walled tubes as energy absorbing structures.